2020
DOI: 10.1155/2020/9546453
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Pattern and Complication Rate of Allergic Fungal Sinusitis: A 10-Year Tertiary Center Experience

Abstract: Background. Allergic fungal rhinosinusitis is a noninvasive form of highly recurrent chronic rhinosinusitis. Despite the advancement in medical and surgical strategies, recurrence in AFRS in general poses another challenging problem with reported incidence that eventually can reach more than 60%. Recognition and understanding the pattern of disease recurrence will lead to greater understanding of the disease response in our population. Method. A retrospective cohort study was performed in King Abdulaziz Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 10 publications
3
20
0
Order By: Relevance
“…In contrast to worldwide studies, a female preponderance is shown in AFRS cases with a mean male percentage of 38.3%. However, the mean age was 20 years, which is concordant with international data [ 21 - 24 ]. Only two studies examined the geographical variations in prevalence.…”
Section: Reviewsupporting
confidence: 89%
See 3 more Smart Citations
“…In contrast to worldwide studies, a female preponderance is shown in AFRS cases with a mean male percentage of 38.3%. However, the mean age was 20 years, which is concordant with international data [ 21 - 24 ]. Only two studies examined the geographical variations in prevalence.…”
Section: Reviewsupporting
confidence: 89%
“…Patients who live in old houses and overcrowded areas are more likely to develop AFRS, as AFRS is most common in patients who live in hot and humid areas such as Jeddah City [ 25 ]. Most patients had nasal polyposis diagnosed before or during ESS for CRS [ 17 , 19 , 21 - 23 ]. A history of bronchial asthma was reported in 9-36% of patients with AFRS [ 17 , 19 - 22 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Allergic fungal sinusitis is mostly considered a disease different chronic sinusitis. It is always associated with nasal polyps [3][4] . Patients with chronic sinusitis are at a higher risk of allergic fungal sinusitis.…”
Section: Introductionmentioning
confidence: 99%